2019
DOI: 10.3895/rbta.v13n2.9532
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do suco de uva da variedade Concord Clone 30 elaborado com novo sistema de extração compatível às pequenas propriedades.

Abstract: O objetivo deste estudo foi avaliar a qualidade e a aceitação sensorial do suco de uva integral da variedade Concord Clone 30 elaborado no equipamento denominado suquificador integral, desenvolvido para pequenas propriedades para substituição de panelas extratoras. Os sucos foram elaborados na cantina experimental da Epagri- Estação Experimental de Videira-SC, empregando as tecnologias de extração: (T1) Extração por sistema adaptado simulando trocador de calor com desengace mecânico das bagas; (T2) Extração po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Comparing the treatments used, it was observed that the integral suquifier (T1) contributed to the greater extraction of total polyphenols and anthocyanins and higher antioxidant activity, for most of the evaluated grape cultivars. Bender et al (2019) observed an opposite behavior with the 'Concord Clone 30' grape cultivar, in which the highest content of total polyphenols and antioxidant activity was achieved using the adapted…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Comparing the treatments used, it was observed that the integral suquifier (T1) contributed to the greater extraction of total polyphenols and anthocyanins and higher antioxidant activity, for most of the evaluated grape cultivars. Bender et al (2019) observed an opposite behavior with the 'Concord Clone 30' grape cultivar, in which the highest content of total polyphenols and antioxidant activity was achieved using the adapted…”
Section: Resultsmentioning
confidence: 86%
“…The highest intensity was found in 'Bordô' grape cultivar regardless of the treatment used. However, comparing the systems, the highest intensity occurred in the juices extracted by the integral suquifier (T1) for most grape cultivars, as observed by Bender et al (2019) in juices from 'Concord Clone 30' grape cultivar. The hue in Table III reflected juices of purple red in 'Bordô' (T1 and T2), 'SCS 421 Paulina' (T1) and 'BRS Carmem' (T2) grape cultivars and red in the other grape cultivars.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations